Objective performance of emergency medical technicians in the use of mechanical cardiopulmonary resuscitation compared with subjective self-evaluation: a cross-sectional, simulation-based study - Wen-Chu Chiang; Matthew Huei-Ming Ma; Yu-Chun Chien; Yao-Cheng Wang; Wen-Shuo Yang; Ping Yen; Wei-Chu Chie (BMJ Open)
Objective To evaluate the subjective and objective resuscitation performance of emergency medical technicians (EMTs) using mechanical cardiopulmonary resuscitation (MCPR) devices.Design and setting This was a cross-sectional simulation-based study where participants installed the MCPR device on a training manikin.Participants We assessed EMT-Intermediates (EMT-Is) and EMT-Paramedics (EMT-Ps) of the Emergency Medical Services (Ambulance) Division of the Taipei City Fire Department.Primary and secondary outcome measures The primary outcome was the gap between self-perceived (subjective) and actual (objective) no-flow time during resuscitation, which we hypothesised as statistically insignificant. The secondary outcome was the association between resuscitation performance and personal attributes like knowledge, attitude and self-confidence.Results Among 210 participants between 21 and 45 years old, only six were female. There were 144 EMT-Is and 66 EMT-Ps. During a simulated resuscitation lasting between four and a half and 5 min, EMTs had longer actual no-flow time compared with self-perceived no-flow time (subjective, 38 s; objective, 57.5 s; p value<0.001). This discrepancy could cause a 6.5% drop of the chest compression fraction in a resuscitation period of 5 min. Among the EMT personal factors, self-confidence was negatively associated with objective MCPR deployment performance (adjusted OR (aOR) 0.66, 95% CI 0.45 to 0.97, p=0.033) and objective teamwork performance (aOR 0.57, 95% CI 0.34 to 0.97, p=0.037) for EMT-Ps, whereas knowledge was positively associated with objective MCPR deployment performance (aOR 2.15, 95% CI 1.31 to 3.52, p=0.002) and objective teamwork performance (aOR 1.77, 95% CI 1.02 to 3.08, p=0.043) for EMT-Is. Moreover, regarding the self-evaluation of no-flow time, both self-satisfaction and self-abasement were associated with objectively poor teamwork performance.Conclusions EMTs’ subjective and objective performance was inconsistent during the MCPR simulation. Self-confidence and knowledge were personal factors associated with MCPR deployment and teamwork performance. Both self-satisfaction and self-abasement were detrimental to teamwork during resuscitation.